Review paperSelected problems of skin aging - Olek-Hrab, Karolina; Hawrylak, Alicja; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Skin aging is a physiological process of unclear pathogenesis despite extensive research. Proper understanding of mechanisms involved in the skin aging process is crucial for effective prevention. Two basic independent pathways – an intrinsic and extrinsic one – seem to be important in skin aging. Exposure to ultraviolet irradiation is regarded as the main causative factor within the extrinsic group. Biological effects of ultraviolet exposure are related to the intensity of irradiation and the light wavelength. Early reactions such as erythema and sunburn, as well as delayed effects due to molecular and biochemical skin damage such as dyspigmentation, preneoplastic and neoplastic transformations, should be noted. Therefore proper and effective photoprotection seems to be of special importance.